Neuroresearch: Another form of mixed method - ., Sasmoko; Indrianti, Yasinta; Karsidi, Ravik; Wuisan, Dewi; Ruliana, Poppy (International Journal of Engineering and Technology, 2018)
Research in the field of Social Sciences is an interesting and complex academic study. Social Science research becomes more and more careful when researchers are not stuck with the only focus on the relationship between variables, but more than that is also deeply reviewed dimensions or indicators or items. For those researchers need a complex method that is a mixed method. One form of the Mixed method is called Neuroresearch. Basically, this Neuroresearch method uses content analysis method as qualitative research (exploratory), then deepens the result of content analysis with quantitative research method (explanatory and confirmatory research). Further explanatory and confirmatory research results are deepened through qualitative research in the form of implications of research results to create new policies, new strategies and new efforts through focus group discussion.Â Â